Analisis Intensitas Turbulensi Terhadap Kestabilan Kecepatan Angin Test Section pada Struktur Wind Tunnel - Arif Pratama, Riza; Ikhsan, Muhammad; Wicaksono, Dhimas; Rieza, M. Safiq; Zainal Abidin , Munir (P3M Politeknik Negeri Cilacap, 2025)
Wind tunnels in aerodynamic testing always have very large sizes to avoid high turbulence intensity. Turbulence intensity analysis is used to determine the size of a smaller wind tunnel to be more efficient in limited space. The use of epoxy fiber resin material is because lighter than aluminum with a thickness of 5mm. The purpose of the study was to produce a wind tunnel with a small size with low turbulence intensity and minimize large manufacture costs. The method used is constructive to analyze the wind tunnel design in determining the maximum wind flow speed at test section does not exceed the turbulence intensity limit. The results of the analysis showed that the wind tunnel structure design has the ability to receive an inlet wind flow of 5 m / s with a maximum wind flow speed at the test location of 10.7 m / s. The wind tunnel design cannot exceed the maximum wind flow speed at the test section because it will produce turbulence intensity above 5% which affects the test result.